Pericardial Effusion/Cardiac Tamponade Induced by Peripherally Inserted Central Catheters in Very Low Birth Weight Infants: A Case Report and Literature Review - Hou, Ana; Fu, Jianhua (Frontiers in Pediatrics, 2020)
Background: Although pericardial effusion/cardiac tamponade (PCE/CT) is a rare complication of peripherally inserted central catheters (PICCs), with an incidence of 0. 07–2%, it is associated with high mortality and is often life threatening. We sought to improve understanding of PICC-induced PCE/CT among pediatricians. Case presentation: The clinical data of PICC-associated PCE/CT in a very low birth weight (VLBW) infant were summarized, and the relevant literature was also reviewed. Conclusions: In VLBW infants with a PICC, if unstable respiratory circulatory system states are observed that cannot be explained, such as tachycardia, bradycardia, apnea, hypotension, and metabolic acidosis, PICC-induced PCE/CT should be considered. Early diagnosis and pericardial puncture are key to saving infants' lives.